Mobile-Assisted intercultural competence development: The role of HelloTalk in Chinese EFL education. - Pei Yang; Ziye Yang (PLoS ONE)
This study investigates the impact of HelloTalk, a mobile-assisted language learning (MALL) platform, on the development of intercultural competence (IC) in Chinese English as a Foreign Language (EFL) students. A mixed-methods approach was employed, involving both quantitative surveys and qualitative interviews. Results indicate that the HelloTalk-based intervention significantly improved students' IC, with the most notable gains observed in their knowledge of other cultures and intercultural communication skills. These findings suggest that mobile-assisted intercultural exchange offers a more effective approach to developing IC compared to traditional classroom learning. Qualitative data further highlight students' positive perceptions of HelloTalk's accessibility, flexibility, and the reduced communication anxiety it fosters. However, challenges such as difficulties in making connections and the potential for deception on mobile platforms were also identified. The study underscores the value of incorporating mobile technologies in EFL curricula to facilitate meaningful intercultural exchanges and improve students' intercultural competence.